A interação nos juizados especiais cíveis: impactos da regulação de conduta no acesso à justiça - Cassundé, Matheus Fernandes (2023)
The research has as its object the rules of interaction of the special civil courts of the metropolitan region of Espírito Santo. The objective is to identify possible effects of the conduct regulation of the special civil courts on access to justice. The hypothesis of the study is that the implementation of the special civil courts has not been accompanied by the loosening/informalization of the regulation of interaction and that certain behavioral statutes existing in the special civil courts create obstacles to access to justice. Erving Goffman's interactionism, the theoretical framework of the research, provided analytical categories for the identification and understanding of aspects of social interaction in general, later confronted with the notion of access to justice built after a literature review of authors such as Cappelletti (1988), Boaventura de Sousa Santos (1977, 1986, 1996) and Jeveaux (2021). Non-participant observation was made of social interaction at hearings in certain special civil courts in the Vila Velha, Cariacica and Serra courts, as well as in the hallways adjacent to the courtrooms. Participant observation and reports of the researcher's professional experience were also described in certain social situations analyzed. The results of the research indicate that the initial hypothesis was partially confirmed, considering that, contrary to what was imagined at first, situational regulation is relatively less firm in the special civil courts, if compared to the ordinary courts, especially regarding personal appearance. The hypothesis was confirmed with regard to the rules regulating the demonstration of deference and communication in court, since in these aspects the behavioral statutes are too firm/formal and confront the notion of access to justice. It was identified the existence of socioeconomic clipping of the postulants of the special civil courts, which suggests that the most vulnerable social categories face prior obstacles and impediments to access to the Judiciary.